PENGARUH PENGGUNAAN STRATEGI GENIUS LEARNING TERHADAP HASIL BELAJAR IPS SISWA KELAS VIII SMP N 4 SUTERA KABUPATEN PESISIR SELATAN TAHUN PELAJARAN 2013 / 2014 - Heryanti, Rani; Nazmi, Ranti; Nurhuda, Ahmad (Pendidikan Sejarah, 2014)
This research is motivated by the learning process is centered social studies teachers , students only listen to what diterang by teachers and less involved in the learning process . Besides the lack of variation in the use of learning methods that fun to be able to attract the attention of students to learn and can enable students to learn. This leads to low yields social studies class VIII SMP N 4 Sutera districts Pesisir Selatan Academic Year 2013/2014 . One strategy that can improve student learning outcomes is the adoption of a strategy Genius Learning . The purpose of this study was to compare the results with the application of social studies students Genius Learning Strategies better than the results of student learning using lecture learning in social studies class VIII SMP N 4 Sutera districts Pesisir Selatan Â . This study is experimental . The study was conducted in SMP N 4 Sutera in August-September first half of the school year 2013/2014 . The population in this study were all students of class VIII SMP 4 Sutera enrolled in the first semester of academic year 2013/2014 . Sampling was done by cluster sampling in order to obtain class VIII1 as the experimental class and the control class as a class VIII2 . The results showed that students learning outcomes IPS experimental class higher than the control class . Experimental class scored an average is 77.52 while the control class scored an average of 70.86 . hypothesis test with the t-test obtained thitung price ( 2.64 ) > t table ( 1.67 ) so that Ho refused and H1 accepted , this means the hypothesis is accepted . It can be concluded that there are differences in learning outcomes of students who use the learning method Genius leraning the lecture method of teaching social studies in the eighth grade students of SMPN 4 Sutera districts Pesisir Selatan. Experimental class scored an average of 77.52 is higher than the results of grade social studies students gain control of the average value of 70.86 . Implementation of this strategy will help students to remember , increase understanding and provide new insights on the subject matter . So the application of learning methods Genius Learning in the learning process can improve learning outcomes .